Interoception and Social Connection - Arnold, Andrew J.; Winkielman, Piotr; Dobkins, Karen (Frontiers in Psychology, 2019)
Interoception—the process of sensing bodily signals, has gained much interest in recent years, due to its role in physical and mental well-being. Here, we focus on the role of interoception in social connection, which is a relatively new and growing research area. Studies in this area suggest that interoception may help in appraising physiological signals in social situations, but also that (challenging) social situations may reduce interoceptive processing by shifting attention from internally- to externally-focused. We discuss potential mechanisms for the influence of interoception on social connection and highlight that flexibility in engaging interoception in social situations may be particularly important. We end with a discussion of loneliness—an extreme case of poor social connection, which is associated with physiological decline and increased mortality risk, and propose that interoceptive dysregulation is involved. We suggest that interventions aimed to improve interoceptive abilities, such as mindfulness-based meditation practices, may be key for alleviating loneliness and improving social connection.